'Tricle' epoxy coffee table from light hardwood / Nor Iryani Ibrahim - Ibrahim, Nor Iryani (2020)
Wood residue mostly produced during sawmilling or an excess part from furniture production. By using wood residue can lead in reducing wood waste which one of the important matters in wood-based industries. Industries nowadays encourage manufacturer to use more wood residue instead of abandoned it. The objective of this study is to design and produce a 'Tricle' Epoxy Coffee Table from Light Hardwood and also to determine customer satisfaction. Due to the development in new technologies along with the Industrial Revolution 4.0, customers tend to attract with a furniture that has aesthetic design, ergonomics and anthropometric features as well as the types of material use. For example, in this study, light hardwood, metal and epoxy resin are used to fulfil the objectives. Epoxy resin and mix of light hardwood had been used as the raw material in order to produce a 'Tricle' Epoxy Coffee Table from Light Hardwood. Recently, epoxy resin becomes a popular material in producing a furniture which had been applied in this study. The result been analysed which involved 107 correspondents that come from different gender, age and profession. There is no significant different according to gender, age group and profession on the characteristics of 'Tricle' Epoxy Coffee Table from Light Hardwood. Most of the correspondents gives rating at 4 (Agree) due to all correspondents had the same opinion toward the idea of the product. For conclusion, 'Tricle' Epoxy Coffee Table from Light Hardwood has been accepted and achieved positive feedbacks from the correspondents regarding the design, material and satisfaction. There are also a few recommendations been suggested to improve the product in future study regarding the colour and material used.